Epidemiological Determinants of Cranioencephalic Trauma in Children - Gonçalves, Daniel Victor Lima; Leite, Pedro de Sousa; Magalhães, Bráulio Filgueira; Cruz, Emanuela Fonseca; Cruz, Amanda Fonseca; Balduino, Cicero Hyttallo Hyttallo Carneiro; Saraiva, Emanuelly Gonçalves; Alencar, Thiago Moreira de; Feitosa, Natália Moreira Garcia; Feitosa, Virgínia Moreira Garcia (Amadeus International Multidisciplinary Journal, 2019)
This article aims to evaluate the epidemiological determinants of TBI in pediatric patients. An integrative review was performed by searching indexed articles in the Virtual Health Library, in which analysis after final analysis included 08 articles. For better elucidation, two categories were formulated: Epidemiological profile of children with TBI and Epidemiological determinants and the clinical implications of TBI in children. It was possible to verify that there is a male predominance, the fall is considered the main mechanism for the condition and TBI, in addition, age groups under 5 years have a worse prognosis. Keywords: Craniocerebral Trauma; Child; Epidemiologic Factors.